Disabling Power of Class and Ideology: Analyzing War Injury through the Transnational Disability Theory and Praxis - Sona Kazemi (Disability Studies Quarterly, 2019)
My doctoral thesis, through a case study of the theocratic-nationalist politics of the Iranian regime and the imperialist politics of the U.S., Russia, and Western Europe in the Middle East, investigated the ways in which gendered-, ideological-, and raced social-relations sustain armed conflicts and generate disability/injury. The study contributed to the emerging field of materialist/Marxist disability studies and critical race moves in disability studies by engaging the dialectics of geopolitics in order to contextualize war, and by proposing a new transnational theory for theorizing disability. In this paper, I extensively discuss my theoretical framework, along with the methodology for collecting and analyzing data in order to offer a radical alternative research method to traditionally biomedical, post-conventionist, liberal, and bourgeois approaches to disability. Additionally, I discuss how I built the new model using the case study in details while introducing its core theoretical constructs emerging directly from the case study. My conceptualization of a transnational theory/model interrogates the violence of the global political economy in producing disablement on a global scale. Finally, I discuss possible directions for further development of the transnational disability model not just as a theory, but also as praxis, active revolutionary knowledge, and political consciousness.
Keywords: dialectical and historical materialism; transnational disability model; Iran-Iraqi War; imperialism; theocratic nationalism; class consciousness